Squaramide-Based 5'-Phosphate Replacements Bind to the DNA Repair Exonuclease SNM1A - McGouran, Joanna; Dürr, Eva-Maria; Doherty, William; Lee, Sook Y.; El-Sagheer, Afaf; Shivalingam, Arun; McHugh, Peter J.; Brown, Tom (My University, 2018)
Phosphate groups are often crucial to biological activity and interactions of oligonucleotides, but confer poor membrane permeability. In addition, the group's lability to enzymatic hydrolysis is an obstacle to its use in therapeutics and in biological tools. We present the synthesis of N‐oxyamide and squaramide modifications at the 5’‐end of oligonucleotides as phosphate replacements and their biological evaluation using the 5’‐exonuclease SNM1A. The squaryl diamide modification showed minimal recognition as a 5’‐phosphate mimic; however, modest inhibition of SNM1A, postulated to occur through metal coordination at the active site, was observed. Their facile incorporation after solid‐phase synthesis and recognition by the exonuclease makes squaryl diamides attractive neutral 5’‐phosphate replacements for oligonucleotides. This work is the first example of squaryl diamide modifications at the 5’‐terminal position of oligonucleotides and of the potential use of modified oligonucleotides to bind to the metal center of SNM1A.
PUBLISHED
Keywords: Exonuclease; Metalloenzyme; 5'-modification; Oligonucleotide; Squaramide